An Unusual “Collision Tumour” of the Prostate Gland and Rectum - C. F. Healy; D. Ferguson; M. F. Mohammed; J. Waterhouse; A. C. Harris (Canadian Journal of Gastroenterology and Hepatology)
Collision tumours of two different histopathological processes are rare. We describe a case of a patient with known low grade prostate adenocarcinoma developing a rectal GIST, which was diagnosed with combined imaging modalities of MR and ultrasound and confirmed by transrectal ultrasound guided biopsy.